2015
DOI: 10.1371/journal.pone.0125935
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in Obese Children: Contribution of Hyperlipidemia, Obesity-Inflammation, and Insulin Sensitivity

Abstract: BackgroundEvidence shows a high incidence of insulin resistance, inflammation and dyslipidemia in adult obesity. The aim of this study was to assess the relevance of inflammatory markers, circulating lipids, and insulin sensitivity in overweight/obese children.MethodsWe enrolled 45 male children (aged 6 to 13 years, lean control = 16, obese = 19, overweight = 10) in this study. The plasma total cholesterol, HDL cholesterol, triglyceride, glucose and insulin levels, the circulating levels of inflammatory factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 58 publications
3
48
2
1
Order By: Relevance
“…To our knowledge, our study is the first one to report the association of maternal GDM with inflammatory markers in prepubertal children. Low-grade inflammation was more evident among obese or overweight children, which is in agreement with previous studies [13, 19]. However, in our study, hs-CRP was higher also in normal-weight GDM children than in control children.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To our knowledge, our study is the first one to report the association of maternal GDM with inflammatory markers in prepubertal children. Low-grade inflammation was more evident among obese or overweight children, which is in agreement with previous studies [13, 19]. However, in our study, hs-CRP was higher also in normal-weight GDM children than in control children.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, there are no previous reports on low-grade inflammation in the GDM offspring studied at prepubertal age, though inflammation is known to be important in the pathogenesis of childhood MetS [13, 19]. In the current study, we investigated the influence of maternal GDM in young children at the median age of 7 years in respect of anthropometric characteristics, lipid and glucose metabolism, and low-grade inflammation.…”
Section: Introductionmentioning
confidence: 97%
“…This finding has been observed in childrenwith central obesity; these changes are dangerous and they have been correlated with cardiovasculardisease in the general population [43].The correlationanalysis in this study further revealed that insulin resistance, CRP and sICAM were positively correlated with LDL-c while negatively correlated with HDL-c. These findings are in accordance with Chang et al, and they highlighted that childhood weight should have special early attention because insulin resistance,inflammation and dyslipidemia increase the risk of cardiovascular disease in adults [44]. …”
Section: Discussionsupporting
confidence: 92%
“…The insulin resistance plays a pivotal role in promoting the dysmetabolic state and obesity complications with the chronic low‐grade inflammation underlying these co‐morbidities . The non‐classical HLA‐class I molecule‐g (HLA‐G) has been postulated as an important immune regulator, which both creates a tolerogenic microenvironment at fetal‐maternal interface and reduces the inflammation .…”
Section: Introductionmentioning
confidence: 99%